The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.0956-7976.2005.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Women Underperform Under Stereotype Threat?

Abstract: This study investigated the role of negative thinking as a potential mediator of performance deficits under stereotype threat. After being assigned to a stereotype-threat or a no-threat condition, 60 female participants were asked to complete a difficult math task. Using the thought-listing technique, women under stereotype threat reported a higher number of negative thoughts specifically related to the test and to mathematics compared with women in the no-threat condition. Moreover, women under stereotype thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
234
3
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(261 citation statements)
references
References 29 publications
13
234
3
9
Order By: Relevance
“…Our work also provides evidence that stereotype threat induces task-related thoughts and worries (for converging evidence, see Cadinu et al, 2005) that target phonological aspects of working memory. Using Baddeley's (1986;Baddeley & Logie, 1999) multicomponent model as a framework, one could unpack verbal working memory into a phonological store capable of holding speech-based information and an articulatory control process based on inner speech mechanisms.…”
Section: Discussionsupporting
confidence: 57%
“…Our work also provides evidence that stereotype threat induces task-related thoughts and worries (for converging evidence, see Cadinu et al, 2005) that target phonological aspects of working memory. Using Baddeley's (1986;Baddeley & Logie, 1999) multicomponent model as a framework, one could unpack verbal working memory into a phonological store capable of holding speech-based information and an articulatory control process based on inner speech mechanisms.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, stereotype threat has been shown to activate thoughts of self-doubt (Steele & Aronson, 1995), negative expectancies (Stangor, Carr, & Kiang, 1998), feelings of dejection (Keller & Dauenheimer, 2003;Marx & Stapel, 2006b), and task-related worries (Beilock et al, 2007). Similarly, Cadinu, Maass, Rosabianca, and Kiesner (2005) showed that women taking a difficult math test reported having more negative thoughts under stereotype threat. Moreover, the number of negative thoughts they had during the first half of the test mediated the effect of stereotype threat on lower performance during the second half of the test.…”
Section: Thought-suppression Processes Tax Working Memorymentioning
confidence: 98%
“…Perhaps some kind of general anxiety causes a general decrement in women's math performance (8). Stereotype threat (ST) has been shown to increase arousal (9), increase negative thoughts (3,10), decrease cognitive resources (5), and increase the perseverance of incorrect problem-solving strategies (11)(12)(13); all of these reactions partially explain performance decrements. Given the varied negative responses to threat, it seems a natural extrapolation to guess that it might inhibit women's ability to learn new information.…”
Section: Gender | Math | Visual Searchmentioning
confidence: 99%